Effect of Cryopreserved Cord Blood Serum on Systemic Inflammatory Responses in Experimental Cold Wound - Kovalov, Gennadii A.; Ischenko, Irina O.; Tynynyka, Lyudmila N.; Iefimova, Irina A.; Vvedenskiy, Boris P.; Sandomirskiy, Boris P. (Problems of Cryobiology and Cryomedicine, 2017)
The effect of cryopreserved cord blood serum on systemic inflammatory responses following skin cryodestruction was studied. The investigation comprised the assessment of inflammation response indices: erythrocyte sedimentation rate, leukogram, amount of C-reactive protein and TBA reactive substances in blood serum after the treatment with the human cryopreserved cord blood serum of animals with cold wounds. It has been shown that cryodamage of rat skin led to an inflammation response accompanied with a two-fold erythrocyte sedimentation rate, 1.5 elevation of C-reactive protein to observation days 7 and 14, changes in leukogram; 1.4 rise in the level of peroxidation processes to day 7, 2.5 times to day 9, 1.9 times to day 14 and 1.5 times to day 21. Application of cryopreserved cord blood serum resulted in a reduced intensity of inflammation response to skin cryodestruction in experimental animals, that was confirmed by a 1.5 time decrease in the level of C-reactive protein to days 7and 9, and its normalization to day 14; 2.0 times diminishing of erythrocyte sedimentation rate to day 7 and its normalization to day 14; normalization of leukogram to day 7; 1.4 times reduction of TBA reactive product level to day 7 and its normalization to day 9. Probl Cryobiol Cryomed 2017; 27(1): 71-80